MINDFULNESS SEBAGAI STRATEGI BAGI PELAKU PARIWISATA UNTUK MENGHADAPI RASA FRUSTRASI DI MASA PANDEMI - Gusti Ayu Ryana Mahasari (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
Even though the Covid 19 pandemic has been going on for 1.5 years, its impact is still being felt today. Especially having an impact on tourism actors who quit or are dismissed from work will experience stress and frustration if they do not have a good emotional control strategy. This study examines one strategy to control emotions, namely mindfulness. This study aims to describe mindfulness as a strategy for tourism actors to deal with frustration during the pandemic. Data were collected by studying literature from various scientific journals. The results show that mindfulness is very relevant and has an important role in controlling emotions so that certain psychological situations such as frustration and stress do not occur.Keywords: Tourism, Pandemic, Mindfulness,